Karakteristik Gelatin Tulang Ikan Patin dengan Spektrofotometer FTIR (Fourier Transform Infra Red) - ira oktaviani rz; Fathul Jannah; Rahimatul Uthia; Untung Triadhi; Rindia Maharani Putri; Annisa Fauzana (LPPM Universitas Abdurrab, 2025)
Gelatin is widely used in the food, pharmaceutical and cosmetic industries. The demand for gelatin is increasing every year, specifically gelatin from pork and beef is the main source of gelatin on the market. Gelatin from fish has become a better prospect to be developed, yet the manufacture of gelatin using organic materials has not been widely used. One of the natural ingredients that can be used in the manufacture of gelatin is from pineapple skin. Pineapple is one of the fruits that contain acids including citric acid and bromelain enzymes which have a high ability to convert collagen protein into gelatin. In this study, a characterization of the gelatin quality of catfish (Pangasius hypopthalmus) bones was carried out which was soaked with pineapple waste liquid with a time difference of 6 hours (P1), 12 hours (P2), and 24 hours (P3). The quality characteristics of gelatin include proximate characteristics, physicochemical characteristics and identification of functional groups using Fourier Transform Infra Red (FTIR) spectrophotometry. The results of this study indicate the percent yield of each of the results of the immersion P1, P2, and P3 that are 0.36%; 0.42% and 0.71%, the results of the water content are 12.20%,; 15.91%, and 12.08%, the results of the ash content are 34.38%,; 30.03%; and 30.00%, protein content are 32.59%; 20.57%, and 23.99%, the pH results are 5.80; 4.71; and 4.77, the viscosity results are 0.959cP, 0.997 cP, and 0.972 cP, respectively. Based on the FTIR spectrum, the functional groups of catfish bone gelatin that can be identified include the O-H, N-H, C-N, C=O, C-H groups. From the results obtained, it can be concluded that the bone gelatin of catfish (Pangasius hypopthalmus) has not fully met the quality standard of gelatin.